The Use of Chitosan-Based Nanoformulations for Controlling Fungi during Storage of Horticultural Commodities - Van Den Broek Lambertus A. M; Boeriu Carmen G (Chitin and Chitosan, 2020)
Biodegradable antimicrobial compounds, such as chitosan, integrated with essential oils, plant extracts, and propolis, have been incorporated into a diverse range of formulations. Likewise, there are various microorganisms that cause serious economic damage, principally during storage of horticultural commodities. Coatings have become increasingly more important as a means to deliver fresh horticultural commodities to the consumer, in safe conditions. Furthermore, studies have confirmed that their applications on agricultural products have a remarkable potential to inhibit microorganisms as compared to the uncoated products. In addition, generally there have been no reports of adverse or side effects on the ripening process of the horticultural products. Currently, the application of nanotechnology has shown great benefits in different fields, such as medicine, energy, the environment, and food. In the latter, the study of food conservation and control of microorganisms that cause decay and disease, through the designing of new materials (nanostructured coatings, among others) has been noteworthy. Regarding this subject, the research group of the Postharvest Technology Laboratory of Agricultural Products of the Center for the Development of Biotic Products (CEPROBI‐IPN) has considered the design and application of nanomaterials as the main theme of their research, based on nontoxic and naturally occurring compounds, focusing on the control of the principal postharvest microorganisms.